Photovoltaic coating, preparation method, application and photovoltaic device

By adjusting the composition composition and preparation method of photovoltaic coatings and optimizing the coating composition, the problem of difficult to take into account both the weather resistance and other properties of the coating in the prior art is solved, and a significant improvement in the high-performance coating and a reduction in the amount of anti-ultraviolet agents are achieved.

CN119144232BActive Publication Date: 2025-04-11JIANGSU DONGTAI TIANTENG ALUMINUM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411642442.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-04-11
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

When existing photovoltaic stent coatings improve weather resistance, they can easily lead to degradation of other coating properties, and the price of anti-ultraviolet agents is high, making it difficult to take into account both high coating performance and low anti-ultraviolet agent usage.

Method used

By adjusting the raw material composition, dosage and preparation method of the coating composition, raw materials such as marinic acid modified rosin resin, nano-silica modified epoxy resin, pigment filler, plasticizer, anti-ultraviolet agent, dispersant and additives are used to optimize the coating formula, significantly improve the coating performance, and reduce the use of anti-ultraviolet agents.

Benefits of technology

While achieving significant improvement in coating performance, the use of anti-UV agents is reduced, and the cost increases are avoided, and the possibility of industrial production is provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a photovoltaic coating, a preparation method, an application and a photovoltaic device, which relates to the field of photovoltaic anticorrosive coatings, and includes the following raw materials: maleic acid modified rosin resin, nano-silicon dioxide modified epoxy resin, pigments and fillers, plasticizers, anti-ultraviolet agents, dispersants and additives; wherein the pigments and fillers include carbon black, rutile titanium dioxide and precipitated barium sulfate; and the additives include nano-silicon dioxide and polyoxyethylene stearate. The present invention improves the comprehensive performance of the coating and reduces the cost by optimizing the coating formulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photovoltaic anti-corrosion coatings, and specifically relates to a photovoltaic coating, a preparation method, an application and a photovoltaic device. Background Art

[0002] Photovoltaic brackets are special brackets designed for placing, installing and fixing solar panels in solar photovoltaic power generation systems. They are generally made of aluminum alloy, carbon steel and stainless steel. However, since photovoltaic brackets are installed outdoors, they need to face various harsh environments for a long time. The working environment of the photovoltaic brackets themselves determines that they will be exposed to more sunlight and rain erosion, and are more prone to corrosion and damage. If there is a lack of targeted anti-corrosion treatment, the maintenance cost of the photovoltaic brackets will inevitably become high and the consumption will be serious.

[0003] Coating is an efficient means of anti-corrosion of photovoltaic brackets and is one of the important research directions for technicians in this field. Existing technologies such as literature: Zhang Zhiwei, Wang Xudong, Ren Yu, et al. Application of water-based inorganic zinc-rich coatings in anti-corrosion of coastal photovoltaic power station brackets [J]. Solar Energy, 2022, (4): 140-146. The corrosion resistance and various properties of four different formulations of water-based inorganic zinc-rich coatings were tested. The results showed that when the zinc content of the prepared new water-based inorganic zinc-rich coating was 81.7% and the content of graphene nanomaterials was 0.8%, the adhesion, pencil hardness and flexibility were significantly improved, the coating appearance and film-forming properties were more intact, and the corrosion resistance was greatly improved. The research results can provide reliable anti-corrosion technical support for steel structure brackets of coastal photovoltaic power stations.

[0004] However, the above paper mainly studies the corrosion resistance of water-based non-electrode zinc-rich coatings and the adhesion between the coating and the substrate, and does not discuss the weather resistance required for photovoltaic brackets, which happens to be a shortcoming of zinc-rich coatings.

[0005] For example, patent application CN117822078A provides a corrosion-resistant photovoltaic bracket and its preparation process. Specifically, the following steps are included: S1: pre-treat the aluminum alloy photovoltaic bracket with zinc immersion to obtain photovoltaic bracket I; S2: perform micro-arc oxidation treatment on photovoltaic bracket I, and obtain photovoltaic bracket II after cleaning and drying; S3: apply a waterproof and corrosion-resistant coating to the surface of photovoltaic bracket II, and wait for drying and curing to obtain a corrosion-resistant photovoltaic bracket. The present invention first removes the uneven oxide film on the surface of the photovoltaic bracket by zinc immersion, and then generates an excellent corrosion-resistant film on its surface by micro-arc oxidation treatment, and finally applies a layer of waterproof and corrosion-resistant coating on the surface of the photovoltaic bracket to protect it.

[0006] When the inventors were studying how to provide a erosion-resistant and UV-resistant coating composition, they found that simply increasing the amount of anti-UV agent added to improve weather resistance would lead to a decrease in other properties of the coating. At the same time, the price of anti-UV agents is generally high. Therefore, a coating composition that takes into account both high coating performance and low anti-UV agent is desired. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a photovoltaic coating, a preparation method, an application and a photovoltaic device. By adjusting the raw material composition, raw material dosage and preparation method of the coating composition based on the technical solution of patent CN116200123B, the performance of the coating is significantly improved and the use of anti-ultraviolet agents is reduced.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0009] The present invention provides a photovoltaic coating, characterized in that it comprises the following raw materials:

[0010] Maleic acid modified rosin resin, nano-silica modified epoxy resin, pigments and fillers, plasticizers, UV inhibitors, dispersants and additives;

[0011] The pigments and fillers include carbon black, rutile titanium dioxide and precipitated barium sulfate; the additives include nano silicon dioxide and polyoxyethylene stearate.

[0012] Furthermore, the photovoltaic coating comprises the following raw materials by weight: 24-36 parts of maleic acid modified rosin resin, 12-24 parts of nano-silicon dioxide modified epoxy resin, 14-20 parts of pigments and fillers, 6-18 parts of plasticizers, 0.8-3 parts of anti-ultraviolet agents, 14-20 parts of dispersants and 8-12 parts of additives.

[0013] Preferably, the photovoltaic coating comprises the following raw materials by weight: 26-34 parts of maleic acid modified rosin resin, 14-22 parts of nano-silicon dioxide modified epoxy resin, 16-18 parts of pigments and fillers, 8-16 parts of plasticizers, 0.8-2 parts of anti-ultraviolet agents, 15-19 parts of dispersants and 9-11 parts of additives.

[0014] Further preferably, the photovoltaic coating comprises the following raw materials, by weight: 30 parts of maleic acid modified rosin resin, 18 parts of nano-silicon dioxide modified epoxy resin, 17 parts of pigments and fillers, 12 parts of plasticizers, 1 part of anti-ultraviolet agent, 17 parts of dispersants and 10 parts of additives.

[0015] Furthermore, the mass ratio of the carbon black, rutile titanium dioxide and precipitated barium sulfate is 0.8-1.1:1.8-2.2:3.7-4.3.

[0016] Preferably, the mass ratio of the carbon black, rutile titanium dioxide and precipitated barium sulfate is 1:2:4.

[0017] Furthermore, the mass ratio of the nano silicon dioxide to polyoxyethylene stearate is 3-5:1.

[0018] Preferably, the mass ratio of the nano-silicon dioxide to polyoxyethylene stearate is 4:1.

[0019] Furthermore, the plasticizer includes at least two of epoxidized soybean oil, trioctyl trimellitate, diisononyl phthalate, dicyclohexyl phthalate and diisodecyl phthalate; the anti-ultraviolet agent includes one or more of calcium zinc stabilizer, epoxy stabilizer, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate and tris(2,4-di-tert-butylphenyl) phosphite; the dispersant includes one or more of fatty acid monoglyceride, isobutyl acetate, lecithin, carboxymethyl cellulose and hydroxypropyl methylcellulose.

[0020] Furthermore, the present invention also provides a method for preparing the above photovoltaic coating, comprising the following steps:

[0021] (1) mixing maleic acid modified rosin resin, nano-silica modified epoxy resin, part of dispersant and additive, and grinding to obtain material A;

[0022] (2) mixing the plasticizer, anti-ultraviolet agent, pigment and filler and the remaining dispersant, and grinding to obtain material B;

[0023] (3) Mix material A and material B to obtain.

[0024] Furthermore, the mixing conditions in step (1) are: stirring at 45-60°C and 500-550 rpm for 15-20 min; and the mixing conditions in step (2) are: stirring at 400-450 rpm for 1-2 h.

[0025] Preferably, the mixing conditions in step (1) are: stirring at 50° C. and 550 rpm for 18 min; and the mixing conditions in step (2) are: stirring at 450 rpm for 1.5 h.

[0026] Furthermore, the photovoltaic coating provided by the present invention or the photovoltaic coating prepared by the preparation method can be used in photovoltaic equipment.

[0027] Furthermore, the present invention also provides a photovoltaic device, the surface of which is coated with the above-mentioned photovoltaic coating or the photovoltaic coating prepared by the above-mentioned preparation method.

[0028] Furthermore, the photovoltaic device is a photovoltaic bracket.

[0029] The technical effects achieved by the present invention are:

[0030] The present invention significantly improves the performance of the coating and reduces the use of anti-ultraviolet agents by adjusting the raw material composition, raw material dosage and preparation method of the coating composition based on the technical solution of patent CN116200123B. By optimizing the coating formulation, the comprehensive performance of the coating is improved, and at the same time, the cost increase caused by the addition of excessive anti-ultraviolet agents is avoided, providing the possibility for later industrial production. DETAILED DESCRIPTION

[0031] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0032] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are for describing specific embodiments rather than for limiting the scope of protection of the present invention.

[0033] When the embodiment gives a numerical range, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs.

[0034] It is worth noting that the maleic acid modified rosin resin (model 442#) used in the present invention is supplied by Zhangjiagang Sunshine Chemical Co., Ltd.; the supplier of nano-silica modified epoxy resin is Xuancheng Jingrui New Materials Co., Ltd.; the cyclodextrin modified nano-silica is α-cyclodextrin modified nano-silica (article number 352352), supplied by Xi'an Qiyue Biotechnology Co., Ltd.;

[0035] The sources of pigments and fillers are not limited. The carbon black used in the present invention has a specification of D90 10 μm, the precipitated barium sulfate has a specification of 2000 mesh, and the rutile titanium dioxide residue (45 μm sieve hole) is ≤0.02%.

[0036] The remaining raw materials are all common commercially available products, so their sources are not specifically limited.

[0037] Example 1

[0038] A photovoltaic coating is composed of the following raw materials, measured by weight: 30 parts of maleic acid modified rosin resin, 18 parts of nano-silicon dioxide modified epoxy resin, 17 parts of pigments and fillers (carbon black, rutile titanium dioxide and precipitated barium sulfate in a mass ratio of 1:2:4), 12 parts of plasticizers (epoxidized soybean oil and diisodecyl phthalate in a mass ratio of 1:1), 1 part of anti-ultraviolet agent (poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) succinate), 17 parts of dispersants (fatty acid monoglyceride) and 10 parts of additives (nano-silicon dioxide and polyoxyethylene stearate in a mass ratio of 4:1).

[0039] The preparation method of the photovoltaic coating is specifically the following steps:

[0040] (1) Mixing maleic acid-modified rosin resin, nano-silica-modified epoxy resin, part of dispersant and additive at 50° C. and 550 rpm for 18 min, and grinding to obtain material A;

[0041] (2) The plasticizer, anti-ultraviolet agent, pigment and filler and the remaining dispersant were stirred at 450 rpm for 1.5 h and then ground to obtain material B;

[0042] (3) Mix material A and material B to obtain.

[0043] Example 2

[0044] A photovoltaic coating is composed of the following raw materials, measured by weight: 24 parts of maleic acid modified rosin resin, 12 parts of nano-silicon dioxide modified epoxy resin, 14 parts of pigments and fillers (carbon black, rutile titanium dioxide and precipitated barium sulfate in a mass ratio of 1:2:4), 6 parts of plasticizers (trioctyl trimellitate, diisononyl phthalate and dicyclohexyl phthalate in a mass ratio of 1:1:1), 0.8 parts of anti-ultraviolet agent (tris (2,4-di-tert-butylphenyl) phosphite), 14 parts of dispersants (isobutyl acetate and lecithin in a mass ratio of 1:1) and 8 parts of additives (nano-silicon dioxide and polyoxyethylene stearate in a mass ratio of 4:1).

[0045] The preparation method of the photovoltaic coating is specifically the following steps:

[0046] (1) Mixing maleic acid-modified rosin resin, nano-silica-modified epoxy resin, part of dispersant and additive at 45° C. and 550 rpm for 15 min, and grinding to obtain material A;

[0047] (2) The plasticizer, anti-ultraviolet agent, pigment and filler and the remaining dispersant were stirred at 400 rpm for 2 h and then ground to obtain material B;

[0048] (3) Mix material A and material B to obtain.

[0049] Example 3

[0050] A photovoltaic coating is composed of the following raw materials, measured by weight: 36 parts of maleic acid modified rosin resin, 24 parts of nano-silicon dioxide modified epoxy resin, 20 parts of pigments and fillers (carbon black, rutile titanium dioxide and precipitated barium sulfate in a mass ratio of 1:2:4), 18 parts of plasticizers (dicyclohexyl phthalate and diisodecyl phthalate in a mass ratio of 2:3), 3 parts of anti-ultraviolet agents (poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate and tris(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:2), 20 parts of dispersants (carboxymethyl cellulose and hydroxypropyl methylcellulose in a mass ratio of 1:1) and 12 parts of additives (nano-silicon dioxide and polyoxyethylene stearate in a mass ratio of 4:1).

[0051] The preparation method of the photovoltaic coating is specifically the following steps:

[0052] (1) Mixing maleic acid-modified rosin resin, nano-silica-modified epoxy resin, part of dispersant and additive at 60° C. and 500 rpm for 20 min, and then grinding to obtain material A;

[0053] (2) The plasticizer, anti-ultraviolet agent, pigment and filler and the remaining dispersant were stirred at 450 rpm for 1 h and then ground to obtain material B;

[0054] (3) Mix material A and material B to obtain.

[0055] Example 4

[0056] A photovoltaic coating is composed of the following raw materials, measured by weight: 26 parts of maleic acid modified rosin resin, 14 parts of nano-silicon dioxide modified epoxy resin, 16 parts of pigments and fillers (carbon black, rutile titanium dioxide and precipitated barium sulfate in a mass ratio of 0.8:1.8:3.7), 8 parts of plasticizers (epoxidized soybean oil and trioctyl trimellitate in a mass ratio of 1:2), 0.8 parts of anti-ultraviolet agent (tris (2,4-di-tert-butylphenyl) phosphite), 15 parts of dispersant (isobutyl acetate) and 9 parts of additives (nano-silicon dioxide and polyoxyethylene stearate in a mass ratio of 3:1).

[0057] The preparation method of the photovoltaic coating is specifically the following steps:

[0058] (1) Mixing maleic acid-modified rosin resin, nano-silica-modified epoxy resin, part of dispersant and additive at 45° C. and 550 rpm for 15 min, and grinding to obtain material A;

[0059] (2) The plasticizer, anti-ultraviolet agent, pigment and filler and the remaining dispersant were stirred at 400 rpm for 2 h and then ground to obtain material B;

[0060] (3) Mix material A and material B to obtain.

[0061] Example 5

[0062] A photovoltaic coating is composed of the following raw materials, measured by weight: 34 parts of maleic acid modified rosin resin, 22 parts of nano-silicon dioxide modified epoxy resin, 18 parts of pigments and fillers (carbon black, rutile titanium dioxide and precipitated barium sulfate in a mass ratio of 1.1:2.2:4.3), 16 parts of plasticizers (epoxidized soybean oil, trioctyl trimellitate and diisononyl phthalate in a mass ratio of 1:2:2), 2 parts of anti-ultraviolet agents (poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol) succinate), 19 parts of dispersants (fatty acid monoglycerides) and 11 parts of additives (nano-silicon dioxide and polyoxyethylene stearate in a mass ratio of 5:1).

[0063] The preparation method of the photovoltaic coating is specifically the following steps:

[0064] (1) Mixing maleic acid-modified rosin resin, nano-silica-modified epoxy resin, part of dispersant and additive at 60° C. and 500 rpm for 20 min, and then grinding to obtain material A;

[0065] (2) The plasticizer, anti-ultraviolet agent, pigment and filler and the remaining dispersant were stirred at 450 rpm for 1 h and then ground to obtain material B;

[0066] (3) Mix material A and material B to obtain.

[0067] Application Example 1

[0068] A photovoltaic bracket, the surface of which is coated with the photovoltaic coating of Example 1.

[0069] Application Example 2

[0070] A photovoltaic bracket, the surface of which is coated with the photovoltaic coating of Example 2.

[0071] Application Example 3

[0072] A photovoltaic bracket, the surface of which is coated with the photovoltaic coating of Example 3.

[0073] Application Example 4

[0074] A photovoltaic bracket, the surface of which is coated with the photovoltaic coating of Example 4.

[0075] Application Example 5

[0076] A photovoltaic bracket, the surface of which is coated with the photovoltaic coating of Example 5.

[0077] Comparative Example 1

[0078] A photovoltaic coating, which differs from Example 1 in that the types of pigments and fillers are different, that is, rutile titanium dioxide is replaced by an equal amount of anatase, and precipitated barium sulfate is replaced by an equal amount of natural barium sulfate.

[0079] In terms of weight, the coating is composed of the following raw materials: 30 parts of maleic acid modified rosin resin, 18 parts of nano-silica modified epoxy resin, 17 parts of pigments and fillers (carbon black, rutile and natural barium sulfate in a mass ratio of 1:2:4), 12 parts of plasticizer (epoxidized soybean oil), 1 part of anti-ultraviolet agent (poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol) succinate), 17 parts of dispersant (monoglyceride of fatty acid) and 10 parts of additives (nano-silica and polyoxyethylene stearate in a mass ratio of 4:1).

[0080] Comparative Example 2

[0081] A photovoltaic coating, which differs from Example 1 in that the ratios of various raw materials in the pigments and fillers are different.

[0082] In terms of weight, the coating is composed of the following raw materials: 30 parts of maleic acid modified rosin resin, 18 parts of nano-silica modified epoxy resin, 17 parts of pigments and fillers (carbon black, rutile titanium dioxide and precipitated barium sulfate in a mass ratio of 0.5:2.5:3), 12 parts of plasticizer (epoxidized soybean oil), 1 part of anti-ultraviolet agent (poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol) succinate), 17 parts of dispersant (monoglyceride of fatty acid) and 10 parts of additives (nano-silica and polyoxyethylene stearate in a mass ratio of 4:1).

[0083] Comparative Example 3

[0084] A photovoltaic coating, which differs from Example 1 in that the ratios of various raw materials in the pigments and fillers are different.

[0085] In terms of weight, the coating is composed of the following raw materials: 30 parts of maleic acid modified rosin resin, 18 parts of nano-silica modified epoxy resin, 17 parts of pigments and fillers (carbon black, rutile titanium dioxide and precipitated barium sulfate in a mass ratio of 1.5:1.5:4.5), 12 parts of plasticizer (epoxidized soybean oil), 1 part of anti-ultraviolet agent (poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol) succinate), 17 parts of dispersant (monoglyceride of fatty acid) and 10 parts of additives (nano-silica and polyoxyethylene stearate in a mass ratio of 4:1).

[0086] Comparative Example 4

[0087] A photovoltaic coating, which differs from Example 1 in that the pigment and filler are replaced by an equal amount of additives.

[0088] In terms of weight, the coating is composed of the following raw materials: 30 parts of maleic acid modified rosin resin, 18 parts of nano-silica modified epoxy resin, 12 parts of plasticizer (epoxidized soybean oil), 1 part of anti-ultraviolet agent (poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol) succinate), 17 parts of dispersant (monoglyceride of fatty acid) and 27 parts of additives (nano-silica and polyoxyethylene stearate in a mass ratio of 4:1).

[0089] Comparative Example 5

[0090] A photovoltaic coating, which differs from Example 1 in that the auxiliary agent is replaced by an equal amount of pigments and fillers.

[0091] In terms of weight, the coating is composed of the following raw materials: 30 parts of maleic acid modified rosin resin, 18 parts of nano-silica modified epoxy resin, 27 parts of pigments and fillers (carbon black, rutile titanium dioxide and precipitated barium sulfate in a mass ratio of 1:2:4), 12 parts of plasticizer (epoxidized soybean oil), 1 part of anti-ultraviolet agent (poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol) ester) and 17 parts of dispersant (fatty acid monoglyceride).

[0092] The preparation methods of Comparative Examples 1-5 are the same as those of Example 1, except that the type or amount of raw materials is changed.

[0093] Test Example 1 Physical Properties Test

[0094] The photovoltaic coatings prepared in the above-mentioned embodiments and comparative examples were sprayed on a hot-dip galvanized aluminum alloy plate made of the same material as a conventional commercially available photovoltaic bracket, with a coating thickness of 30 μm, and then the performance of the photovoltaic bracket was examined.

[0095] Neutral salt spray resistance test is carried out according to GB / T 1771-2007 "Determination of neutral salt spray resistance of paints and varnishes";

[0096] Determine the adhesion of the coating according to GB / T 9286-2021 "Scratch test for paint and varnish films";

[0097] Determine the pencil hardness of the coating according to GB / T 6739-2022 "Determination of film hardness of paints and varnishes by pencil method";

[0098] The impact resistance of the coating is measured according to GB / T 1732-2020 "Determination of impact resistance of paint films";

[0099] The flexibility of the coating is measured according to GB / T 1731-2020 "Determination of flexibility of paint films and putty films".

[0100] The test results are shown in Table 1.

[0101] Table 1 Physical properties test results

[0102]

[0103] According to the test results in the above table, the coating of the present invention has excellent salt spray resistance, high adhesion level, strong pencil hardness, impact resistance and flexibility. The coating formulation corresponding to Example 1 has the best effect. Compared with patent CN116200123B, the physical properties of the coating in the present invention are more excellent, and the amount of anti-ultraviolet agent used is also significantly reduced. Compared with the coating of Example 1, when the type of pigments and fillers is changed, its salt spray resistance is significantly reduced, rust spots appear, adhesion is reduced, and the other properties are slightly reduced. When the ratio of each raw material in the pigments and fillers is different, the overall performance is reduced, especially in the impact resistance level. When the raw materials are not added with pigments and fillers and are replaced with additives or no additives are added, the salt spray resistance, pencil hardness, impact resistance and flexibility are significantly reduced, indicating that there is a synergistic effect between pigments and fillers and additives in the coating formulation.

[0104] Test Example 2 Artificially Accelerated UV Aging Test

[0105] The photovoltaic coatings prepared in the above-mentioned embodiments and comparative examples were sprayed on a hot-dip galvanized aluminum alloy plate made of the same material as a conventional commercially available photovoltaic bracket, with a coating thickness of 30 μm, and then the performance of the photovoltaic bracket was examined.

[0106] The test was conducted according to the method described in GB / T 14522-2008 "Artificial weathering test method for plastics, coatings and rubber materials for mechanical industrial products - fluorescent ultraviolet lamp", and the ultraviolet radiation intensity was set to 1.55W / m 2 The coating surface temperature during irradiation was 50°C, and the aging cycle was 500h and 800h. Then, the chromaticity of the coating at the end of different aging cycles was measured according to GB / T 11186.2-1989 "Measurement Methods for Coating Color Part 2: Color Measurement", and the color difference between the coating at the end of different aging cycles and before the aging test was calculated according to GB / T 11186.3-1989 "Measurement Methods for Coating Color Part 3: Color Difference Calculation", and the results are statistically summarized in Table 2.

[0107] Table 2 Artificially accelerated UV aging results

[0108]

[0109] According to the test results in the above table, the coating of the present invention has excellent anti-ultraviolet and anti-aging properties. After the artificial accelerated ultraviolet aging test, the color difference of the coating surface is not obvious. In comparison, the color difference in the other comparative examples varies greatly, especially for comparative examples 3 and 4, the color difference varies significantly, indicating that the anti-ultraviolet and anti-aging properties of the corresponding formulations are poor.

[0110] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A photovoltaic coating, characterized in that: The invention is prepared from the following raw materials by weight: 24-36 parts of maleic acid modified rosin resin, 12-24 parts of nano-silicon dioxide modified epoxy resin, 14-20 parts of pigments and fillers, 6-18 parts of plasticizers, 0.8-3 parts of anti-ultraviolet agents, 14-20 parts of dispersants and 8-12 parts of additives; The pigments and fillers are carbon black, rutile titanium dioxide and precipitated barium sulfate in a mass ratio of 0.8-1.1:1.8-2.2:3.7-4.3; The auxiliary agent is nano silicon dioxide and polyoxyethylene stearate in a mass ratio of 3-5:1; The plasticizer includes at least two of epoxy soybean oil, trioctyl trimellitate, diisononyl phthalate, dicyclohexyl phthalate and diisodecyl phthalate.

2. The photovoltaic coating according to claim 1, characterized in that: The invention is prepared from the following raw materials by weight: 30 parts of maleic acid modified rosin resin, 18 parts of nano-silicon dioxide modified epoxy resin, 17 parts of pigments and fillers, 12 parts of plasticizers, 1 part of anti-ultraviolet agent, 17 parts of dispersants and 10 parts of additives.

3. The photovoltaic coating according to claim 1, characterized in that: The mass ratio of the carbon black, rutile titanium dioxide and precipitated barium sulfate is 1:2:

4.

4. The photovoltaic coating according to claim 1, characterized in that: The anti-ultraviolet agent includes one or more of calcium zinc stabilizers, epoxy stabilizers, polysuccinic acid (4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) ester and tris (2,4-di-tert-butylphenyl) phosphite; the dispersant includes one or more of fatty acid monoglyceride, isobutyl acetate, lecithin, carboxymethyl cellulose and hydroxypropyl methylcellulose.

5. The method for preparing the photovoltaic coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing maleic acid modified rosin resin, nano-silica modified epoxy resin, part of dispersant and additive, and grinding to obtain material A; (2) mixing the plasticizer, anti-ultraviolet agent, pigment and filler and the remaining dispersant, and grinding to obtain material B; (3) Mix material A and material B to obtain.

6. Use of the photovoltaic coating according to any one of claims 1 to 4 or the photovoltaic coating prepared by the preparation method according to claim 5 in photovoltaic equipment.

7. A photovoltaic device, characterized in that: The surface of the photovoltaic device is coated with the photovoltaic coating according to any one of claims 1 to 4 or the photovoltaic coating prepared by the preparation method according to claim 5.

8. The photovoltaic device according to claim 7, characterized in that: The photovoltaic device is a photovoltaic bracket.

Citation Information

Patent Citations

  • Corrosion-resistant photovoltaic support and preparation process thereof

    CN117822078A

  • Epoxy potable water tank paint and its preparation method

    CN103360905A

  • Erosion-resistant and ultraviolet-resistant photovoltaic support, coating composition and preparation method of erosion-resistant and ultraviolet-resistant photovoltaic support

    CN116200123A